The Formation of a Critical Discourse on Polygamy in Iranian Press in the Late Qajar Period - Abbas Ghadimi Gheidari; Neda Sonboli (تاریخ نگری و تاریخ نگاری)
In the late Qajar period, particularly during the constitutional era, the emergence of a more open political and social atmosphere led to the discussion of new issues concerning women—issues that had not been addressed publicly before. This included the question of polygamy, which became the focus of certain newspapers, intellectuals, and educated elites. Research shows that these newspapers and their authors, who saw a change in the status of women as a fundamental prerequisite for  social change in Iran, initiated a critical discourse on traditional women’s issues, including polygamy. The findings of this study demonstrate that these writers employed direct prose, satirical criticism, popular poetry, and caricatures to critique polygamy and examine its social and economic causes and consequences. This article uses thematic analysis of narratives—a method of content analysis- to examine how and why a critical discourse on polygamy emerged in the newspapers and journals of the time, and how this discourse played a significant role in shaping the cultural transformation of Iranian society.